Temporal variability of the meridional overturning circulation at 34.5°S: Results from two pilot boundary arrays in the South Atlantic - Meinen1, Christopher S.; Speich2, Sabrina; Perez1, Renellys C.; Dong, Shenfu; Piola, Alberto R.; Garzoli, Silvia L.; Baringer, Molly O.; Gladyshev, Sergey; Campos, Edmo J. D. (Journal of Geophysical Research: Oceans, 2013)
International audience Data from two boundary arrays deployed along 34.5°S are combined to produce the first continuous in situ time series observations of the basin-wide meridional overturning circulation (MOC) in the South Atlantic. Daily estimates of the MOC between March 2009 and December 2010 range between 3 Sv and 39 Sv (1 Sv = 106 m3 s−1) after a 10 day low-pass filter is applied. Much of the variability in this ∼20 month record occurs at periods shorter than 100 days. Approximately two-thirds of the MOC variability is due to changes in the geostrophic (baroclinic plus barotropic) volume transport, with the remainder associated with the direct wind-forced Ekman transport. When low-pass filtered to match previously published analyses in the North Atlantic, the observed temporal standard deviation at 34.5°S matches or somewhat exceeds that observed by time series observations at 16°N, 26.5°N, and 41°N. For periods shorter than 20 days the basin-wide MOC variations are most strongly influenced by Ekman flows, while at periods between 20 and 90 days the geostrophic flows tend to exert slightly more control over the total transport variability of the MOC. The geostrophic shear variations are roughly equally controlled by density variations on the western and eastern boundaries at all time scales captured in the record. The observed time-mean MOC vertical structure and temporal variability agree well with the limited independent observations available for confirmation.